A DAMPAK KETERBUKAAN EKONOMI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Adi Poernomo; Hari Winarto (FEB UNWIKU PURWOKERTO, 2020)
This study aims to analyze the impact of economic openness on Indonesia's economic growth. The data used are secondary data from Bank Indonesia, the Central Statistics Agency (BPS), the Investment Coordinating Board which is a quarterly time series data from 2008-1 to 2016-4. The variables used in this study include, Economic Growth, Exports, Imports, FDI (Foreign Direct Investment), Foreign and Private Debt. The analytical approach used is the econometric model Vector Error Correction Model (VECM). The results show that exports have a negative effect on long-term economic growth, but the short-term positive effect on economic growth, while imports have a negative effect on economic growth both short-term and long-term, although the lag 2 short-term positive effect. The variable Foreign Direct Investment (FDI) in the short run 1 lag has a negative influence on economic growth, but for the short run 2 lag and the long run the FDI variable has a positive effect on economic growth. Government External Debt Variables (ULP) both in the short and long term lag 1 and 2 have a negative and significant effect on economic growth. The variable Private External Debt (ULS) in the short term has a negative effect on economic growth both lag 1 and lag 2, but for the long term the variable Private External Debt (ULS) has a positive effect on economic growth.